Insidious enemy - phaeochromocytoma. Can diabetes be cured? - Szafrańska, Małgorzata; Główczewska-Siedlecka, Emilia; Siedlecki, Zygmunt (Journal of Education, Health and Sport, 2022)
We present the case of a 54-year-old patient with long-term type 2 diabetes, treated with intensive insulin therapy, who was considered to be ordinary diabetes. In a random imaging examination it turned out to be a phaeochromocytoma. The patient underwent surgical treatment. It turned out that after the surgery, the diabetes resolved. It is a casuistic curiosity that the patient was "cured" of the disease after diagnosis and treatment for pheochromocytoma, and on the second day after the surgery. It is also a valuable guide when looking for all possible causes of "secondary" diabetes.